The Authenticity of the Document at Andocides On the Mysteries 95-98 - Harris, Edward M. (Tekmeria, 2015)
This essays studies the document inserted into the text of Andocides' speech On the Mysteries (96-98) and shows that it is not a genuine copy of the decree of Demophantus from an analysis of its contents and a comparison with the formulas and language of decrees from the late fifth and fourth centuries BCE preserved on stone. The final part of the essay analyzes the historical context of the decree of Demophantus and shows that it belongs in the period where Lycurgus (Against Leocrates 124-127) places it, that is, after the overthrow of the Thirty in 403 BCE.